Delayed onset of tricuspid valve flow in repaired tetralogy of Fallot: an additional mechanism of diastolic dysfunction and interventricular dyssynchrony - Benson Lee N; Redington Andrew N; Bronzetti Gabriele; Cheung Michael; AlHabshan Fahad; Sun Ai-Min; Macgowan Christopher; Yoo Shi-Joon (Journal of Cardiovascular Magnetic Resonance, 2011)
Abstract Background Diastolic dysfunction of the right ventricle (RV) is common after repair of tetralogy of Fallot. While restrictive physiology in late diastole has been well known, dysfunction in early diastole has not been described. The present study sought to assess the prevalence and mechanism of early diastolic dysfunction of the RV defined as delayed onset of the tricuspid valve (TV) flow after TOF repair. Methods The study population consisted of 31 children with repaired TOF (mean age ± SD, 12.3 ± 4.1 years) who underwent postoperative cardiovascular magnetic resonance (CMR). The CMR protocol included simultaneous phase-contrast velocity mapping of the atrioventricular valves, which enabled direct comparison of the timing and patterns of tricuspid (TV) and mitral (MV) valve flow. The TV flow was defined to have delayed onset when its onset was > 20 ms later than the onset of the MV flow. The TV and MV flow from 14 normal children was used for comparison. The CMR results were correlated with the findings on echocardiography and electrocardiography. Result Delayed onset of the TV flow was observed in 16/31 patients and in none of the controls. The mean delay time was 64.81 ± 27.07 ms (8.7 ± 3.2% of R-R interval). The delay time correlated with the differences in duration of the TV and MV flow (55.94 ± 32.88 ms) (r = 0.90, p < 0.001). Delayed onset was associated with prolongation of the RV ejection time in 9 and delayed onset and cessation of the pulmonary arterial flow in 4. Delayed onset was not associated with timing changes in the pulmonary artery in 3. The patients with delayed onset showed reduced RV ejection fraction (p = 0.01). However, the two groups did not show significant differences in TV E/A ratio, ventricular end-diastolic volumes, left ventricular ejection fraction, pulmonary regurgitant fraction, heart rate, PR interval and QRS duration. Conclusions Early diastolic dysfunction with delayed onset of TV flow is common after TOF repair, and is associated with reduced RV ejection fraction. It is a further manifestation of interventricular dyssynchrony and represent an additional mechanism of ventricular diastolic dysfunction.